1996
DOI: 10.4141/cjps96-039
|View full text |Cite
|
Sign up to set email alerts
|

Seeding depth, rate and row spacing for winter wheat grown on stubble and chemical fallow in the semiarid prairies

Abstract: (1986). In d{er years (1987 and 1988) there was rarely any difference due to seeding rate. Narrow.g*.rpu.ing resulted in greater plant density than wide row spacing; however, row spacing had little effect on grain yield. In the semiarid pffi, *here trasl clearance for seeding implements is not usually a problem, and where many producers still swath the crop, it may be advantageous touse a narrow ro* spacing. Howeveq if power requirements and trash clearance are important considerati-ons, *i:d;;; ril;i"g ;1u b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 7 publications
4
29
1
Order By: Relevance
“…It is generally accepted that yield increases when Finger millet rows are narrowly spaced. This, however, is not always supported by the literature (Crabtree and Rupp, 1980;Teich et al, 1993;McLeod et al, 1996;Lafond and Gan, 1999;Hiltbrunner et al, 2004). Intercropping has gained interest because of potential advantages it offers over yielding, i.e.…”
Section: Introductioncontrasting
confidence: 44%
“…It is generally accepted that yield increases when Finger millet rows are narrowly spaced. This, however, is not always supported by the literature (Crabtree and Rupp, 1980;Teich et al, 1993;McLeod et al, 1996;Lafond and Gan, 1999;Hiltbrunner et al, 2004). Intercropping has gained interest because of potential advantages it offers over yielding, i.e.…”
Section: Introductioncontrasting
confidence: 44%
“…Bavec et al (2002) and Geleta et al (2002) reported that protein content of grain decreased with increasing seeding rate. In contrast, Campbell et al (1991) and McLeod et al (1996) reported that protein content of grain was not infl uenced by seeding rate. In the present study, grain protein content was similar at 50 and 150 seeds m -2 (Table 2).…”
Section: Discussionmentioning
confidence: 91%
“…Seeding density affects grain yields and plant density (McLeod et al, 1995). In addition, high seeding density can result in higher grain yields and plant density than low seeding density .…”
Section: Seeding Densitymentioning
confidence: 99%
“…Stougaard and Xue (2003) found that high seeding density increased yield 12%-18% when compared with low seeding density in Montana. Work in Canada showed that a 60 kg ha −1 seeding rate resulted in a 61% higher plant density than a 30 kg ha −1 seeding rate (McLeod et al, 1995). High seeding density can control weed biomass and reestablishment of weeds in ensuing seasons and can compensate for poor plant establishment (Rurnett et al, 2003).…”
Section: Seeding Densitymentioning
confidence: 99%